Thermogenic methane injection via bubble transport into the upper Arctic Ocean from the hydrate-charged Vestnesa Ridge, Svalbard - Smith, Andrew James; Mienert, Jurgen; Bünz, Stefan; Greinert, Jens (Geochemistry, Geophysics, Geosystems, 2014)
An edited version of this paper was published by AGU. Copyright (2014) American Geophysical Union. Smith, A.J., Mienert, J., Bünz, S. & Greinert, J. (2014). Thermogenic methane injection via bubble transport into the upper Arctic Ocean from the hydrate-charged Vestnesa Ridge, Svalbard. Journal of Geophysical Research - Solid Earth. 15(5), 1945-1959. https://doi.org/10.1002/2013GC005179 . We use new gas‐hydrate geochemistry analyses, echosounder data, and three‐dimensional P‐Cable seismic data to study a gas‐hydrate and free‐gas system in 1200 m water depth at the Vestnesa Ridge offshore NW Svalbard. Geochemical measurements of gas from hydrates collected at the ridge revealed a thermogenic source. The presence of thermogenic gas and temperatures of ∼3.3°C result in a shallow top of the hydrate stability zone (THSZ) at ∼340 m below sea level (mbsl). Therefore, hydrate‐skinned gas bubbles, which inhibit gas‐dissolution processes, are thermodynamically stable to this shallow water depth. This was confirmed by hydroacoustic observations of flares in 2010 and 2012 reaching water depths between 210 and 480 mbsl. At the seafloor, bubbles are released from acoustically transparent zones in the seismic data, which we interpret as regions where free gas is migrating through the hydrate stability zone (HSZ). These intrusions result in vertical variations in the base of the HSZ (BHSZ) of up to ∼150 m, possibly making the shallow hydrate reservoir more susceptible to warming. Such Arctic gas‐hydrate and free‐gas systems are important because of their potential role in climate change and in fueling marine life, but remain largely understudied due to limited data coverage in seasonally ice‐covered Arctic environments.